Public Understanding of E-Government Transparency and Accountability and its Influence on Public Participation in Corruption Prevention - Dini Arwaty*; Dini Verdanıa Latif; Syakıeb Arsalan (Universitas Syiah Kuala, 2024)
Corruption cases in Indonesia are considered extraordinary crimes because they can impact many things. Corruption can have an impact on the country's economy, the welfare of citizens, the fulfillment of human rights, and access to the basic needs of citizens. The government has made various efforts such as transparency and accountability in state financial management which is useful for public funds. One way is through E Government. Ironically, the number of corruption cases has never disappeared. In order to effectively eradicate corruption, it is necessary to provide the widest possible space for public participation as control or supervision of government administration in the management of public funds. In order for supervision to be effective, the public needs to first clearly understand the concepts of accountability and transparency. The aim of this research is to determine the public's understanding of e-government accountability and transparency and its influence on public participation as supervisors of public funds managed by the government. This research is quantitative research. The results of this research can provide input in efforts to prevent corruption in Indonesia. The research results show that there is a relationship between public understanding of transparency and accountability and public participation in corrupton prevention.